A possible link between KCNQ2‐ and STXBP1‐related encephalopathies: STXBP1 reduces the inhibitory impact of syntaxin‐1A on M current. (25th October 2017) - Devaux, Jérôme; Dhifallah, Sandra; De Maria, Michela; Stuart‐Lopez, Geoffrey; Becq, Hélène; Milh, Mathieu; Molinari, Florence; Aniksztejn, Laurent
Summary: Objective: Kv7 channels mediate the voltage‐gated M‐type potassium current. Reduction of M current due to KCNQ2 mutations causes early onset epileptic encephalopathies (EOEEs). Mutations in STXBP1 encoding the syntaxin binding protein 1 can produce a phenotype similar to that of KCNQ2 mutations, suggesting a possible link between STXBP1 and Kv7 channels. These channels are known to be modulated by syntaxin‐1A (Syn‐1A) that binds to the C‐terminal domain of the Kv7.2 subunit and strongly inhibits M current. Here, we investigated whether STXBP1could prevent this inhibitory effect of Syn‐1A and analyzed the consequences of two mutations in STXBP1 associated with EOEEs. Methods: Electrophysiologic analysis of M currents mediated by homomeric Kv7.2 or heteromeric Kv7.2/Kv7.3 channels in Chinese hamster ovary (CHO) cells coexpressing Syn‐1A and/or STXBP1 or mutants STXBP1 p.W28* and p.P480L. Expression and interaction of these different proteins have been investigated using biochemical and co‐immunoprecipitation experiments. Results: Syn‐1A decreased M currents mediated by Kv7.2 or Kv7.2/Kv7.3 channels. STXBP1 had no direct effects on M current but dampened the inhibition produced by Syn‐1A by abrogating Syn‐1A binding to Kv7 channels. The mutation p.W28*, but not p.P480L, failed to rescue M current from Syn‐1A inhibition. Biochemical analysis showed that unlike the mutation p.W28*, the mutation p.P480L did not affect STXBP1 expression and reduced the interaction of Syn‐1A with Kv7 channels. Significance: These data indicate that there is a functional link between STXBP1 and Kv7 channels via Syn‐1A, which may be important for regulating M‐channel activity and neuronal excitability. They suggest also that a defect in Kv7 channel activity or regulation could be one of the consequences of some STXBP1 mutations associated with EOEEs. Furthermore, our data reveal that STXBP1 mutations associated with the Ohtahara syndrome do not necessarily result in protein haploinsufficiency.